Pirolisis Kulit Kayu Pinus (Pinus Mercusil) Menjadi Bio-Oil Menggunakan Katalis Ni/Lempung - Laila Kusmiati; Syaiful Bahri; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Requirement for the source of energy which increasing and petroleum reserve as source of primary energy which continuing attenuate to become the main reason for the importance ofsearching for alternative energy sources instead of petroleum. Biomass specially pine bark only considered as waste that pollutes the environment, whereas the pine bark is biomass that can be processed to become alternative energy that is bio-oil. Bio-oil can be produced through pyrolisis process using catalyst Ni/clay. This research aim to study the effect of the ratio of amount of catalyst to biomass which variation to 3%, 5% and 7% b/b and also the effect of Ni metal consentrate on clay equal to 0%, 1%, 2% and 3% w /w of the yield bio-oil produced. In thisresearch, pine bark biomass as much 50 grams with size of --60+80 mesh, silinap 500 ml, and catalyst Ni/clay entered into pyrolisis reactor. Process of pyrolisis is conducted at temperature320 oC and stirring speed of 300 rpm during 120 minute with stream of nitrogen gas (N2) as inert gas. The result obtained indicate that optimum yield obtained at 2% catalyst Ni/clay asmuch as 7% of biomass that is equal to 61,03%. Physical properties test result obtained that is density (0,856 gr/ml), viscosity (9,306 cSt), acidity number (24,986 mg of NaOH/gr of sample) and flash point (54 oC). Result of chemical analysis with GC-MS, obtained the dominant chemical components in bio-oil are 2-Pentene 22,31%, Pentane 13,46%, 1-propene 7,55%, 2- Hexene 7,35 and 1-Pentene 5,95%.Keywords: Biomass, Bio-oil, Catalyst Ni/Clay, Pine Bark, Pyrolysis